THE RELATIONSHIP PERSONAL HYGIENE AND SANITATION ENVIRONMENTAL ON NUTRITIONAL STATUS IN TODDLER AT BULIANG DISTRICT - Sari, Novela; Martha, Elsusi; Fuadi, Asrul; Windusari, Yuanita (Jurnal Ilmu Kesehatan, 2023)
Nutritional status at the Batu Aji Community Health Center is the first problem in Batam City and Buliang Village is the highest among other districts. This research aims to determine the relationship between personal hygiene and environmental sanitation on the nutritional status of toddlers in Buliang Village, Batam City in 2023. This type of research is used is quantitative with a cross sectional research design. The subjects in this research were mothers with toddlers aged 0-59 months who lived in Buliang Village, Batam City. The sampling technique used was Cluster Random Sampling with chi-square test analysis . The results of the chi square test data analysis show that there is a relationship between personal hygiene and nutritional status in toddlers (p value = 0.022), environmental sanitation and nutritional status in toddlers (p value = 0.032). The conclusion from this research is that there is a relationship between personal hygiene and environmental sanitation on the nutritional status of toddlers. It is hoped that the community will be more disciplined in paying attention to toddlers' personal hygiene and environmental sanitation so that they pay attention to fulfilling the environmental sanitation requirements of SPALs and waste disposal sites.